Notebook on cities and clothes (1989) - Wenders, Wim ([USA] : Anchor Bay, 2003)
Contains also 'Twelve Years later' (7 min.) and Wim Wenders bio
English spoken
Onderzoek KASK Professioneel (OFVP)
film
Keywords: Wenders , Wim; Yamamoto, Johji